2012
DOI: 10.1002/lapl.201110124
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength mode-locked erbium-doped fiber laser based on the interaction of graphene and fiber-taper evanescent field

Abstract: We report on the generation of multiwavelength passively mode-locked pulses in an erbium-doped fiber laser (EDFL) based on the interaction of graphene and fiber-taper evanescent field. Graphene-polymer nanocomposites in aqueous suspension are trapped by the optical evanescent light and deposited on taper region. The graphene-deposited fibertaper device not only acts as an excellent saturable absorber for mode-locking, but also induces a polarizing effect to form an artificial birefringent filter for multiwavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 42 publications
2
51
0
Order By: Relevance
“…2. This could be exploited advantageously for Q-switching or mode-locking laser operation by using an acousto-optic modulator [15] or well-known saturable absorbers such as Cr:YAG [16], SESAM [17] or some (now-popular) graphene [18], [19].…”
Section: Resultsmentioning
confidence: 99%
“…2. This could be exploited advantageously for Q-switching or mode-locking laser operation by using an acousto-optic modulator [15] or well-known saturable absorbers such as Cr:YAG [16], SESAM [17] or some (now-popular) graphene [18], [19].…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that the MSC play an important role for dual-wavelength generation. We reckoned that the dual-wavelength generation mechanism may be the combined result of wavelength-dependent gain distribution of the laser and induced birefringence [39], [40] by the MSC owing to its asymmetrical tapering [41]. Wavelength-dependent intracavity loss has been utilized to implement dual-wavelength generation [42].…”
Section: B Dual-wavelength Mode-locking Statementioning
confidence: 99%
“…The presence of terbium ions leads to high (but still not as high as in TGG) absorption at 485 nm and in the longer than 1600 nm wavelength range, but in the 500-1600 nm range the transmittance change is within the instrumental error. Especially draws attention the fact that Tb:CaF 2 retains high transparency in longer wavelengths range than the traditional TGG crystal, which opens up prospects of its use for erbium-doped fiber lasers wavelengths range (''eye-safe'' range 1530-1620 nm) becoming more popular lately [25][26][27].…”
Section: Transmission Spectrummentioning
confidence: 99%